La pedagogía crítica y su influencia en el desarrollo del pensamiento creativo en los estudiantes de séptimo año de educación básica de la unidad educativa Eugenio Espejo del cantón Babahoyo provincia de los Rios. - Vite Cellán, Irvin (2016)
The present thesis has as its theme: Critical pedagogy and the influence in the development of the creative thinking of the students of seventh year of Basic Education of Canton Babahoyo in the academic year 2015-2016. This is composed of 4 chapters, which are detailed as follows: The first chapter outlines the different contexts, the problem, its approach and formulation, the general and specific objectives that have been reasonably developed and the justification of the subject matter. The second chapter is composed of the theoretical framework in which the different foundations such as: conceptual, and theoretical; Referential, investigative antecedents, theoretical posture and also general hypothesis as specific hypotheses. The third chapter indicates the expected results; The presentation of data in tables, graphs and analysis; Conclusions and recommendations based on the results of the surveys to the educational triad ie teachers, students and parents. The fourth chapter presents the proposal as such, "Teaching guide with a focus on critical pedagogy for the development of creative thinking of students seventh year" addressed to the teachers of the Educational Unit Eugenio Espejo. And next the fourth chapter presents the bibliography and linkage of books and web pages used in research and annexes.